Perancangan dan analisis struktur statis terhadap fuselage versi maritim dari prototipe uav v5 produksi - Gabriel Sutantyo; Sheila Tobing; Budi Atmoko (University of Muhammadiyah Jakarta, 2022)
PT. Famindo Inovasi Teknologi (PT. FIT) is a company that works in the drone industry, and currently PT. FIT receives a request from Badan Keamanan Laut Republik Indonesia (BAKAMLA) to design a drone that can float on water. Therefore, my purpose is to design a fuselage of the maritime version from UAV V5 prototype produced by PT. FIT that have a lower fuselage volume of 30 liters and able to withstand a 5G loading. The lower fuselage is designed at 30 liters because the mass of the finished drone is 25 kg. The design will include the shape of the fuselage, rib structure and support structure. After the design is complete, the next step is simulation using Solidworks with static simulation features. The fuselage simulation is done with a mesh size of 8 mm according to the mesh independence test method and 5G loading. The result of the fuselage simulation shows a maximum stress of 17.142 MPa and a maximum displacement of 0.614 mm, so the fuselage of the maritime version from UAV V5 prototype produced by PT. FIT design can be declared as safe.